2000
DOI: 10.1016/s0092-8674(00)00192-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a β-Catenin/Tcf Complex

Abstract: The Wnt signaling pathway plays critical roles in embryonic development and tumorigenesis. Stimulation of the Wnt pathway results in the accumulation of a nuclear beta-catenin/Tcf complex, activating Wnt target genes. A crystal structure of beta-catenin bound to the beta-catenin binding domain of Tcf3 (Tcf3-CBD) has been determined. The Tcf3-CBD forms an elongated structure with three binding modules that runs antiparallel to beta-catenin along the positively charged groove formed by the armadillo repeats. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
380
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(397 citation statements)
references
References 45 publications
12
380
0
5
Order By: Relevance
“…The interaction of various Wnts (Wnt1, Wnt3a, and Wnt8) with their receptors (Fz) and co-receptors (LRP/5/6) triggers the recruitment of Axin to LRP6, promoting the dissociation of β-catenin from Axin and thereby inhibiting β-catenin phosphorylation and its subsequent degradation [33,34]. Biochemical and structural studies have demonstrated that Axin binds to β-catenin at a site on armadillo repeats 3-5 and that Phe253 and Lys292 of β-catenin contribute to this interaction [35][36][37]. In our study, just as in the case of Wnt-mediated Axin inactivation, SKL2001 inhibited both the CK1-and GSK-3β-mediated phosphorylation of β-catenin at Ser45 and Ser33/37/Thr41, respectively, in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of various Wnts (Wnt1, Wnt3a, and Wnt8) with their receptors (Fz) and co-receptors (LRP/5/6) triggers the recruitment of Axin to LRP6, promoting the dissociation of β-catenin from Axin and thereby inhibiting β-catenin phosphorylation and its subsequent degradation [33,34]. Biochemical and structural studies have demonstrated that Axin binds to β-catenin at a site on armadillo repeats 3-5 and that Phe253 and Lys292 of β-catenin contribute to this interaction [35][36][37]. In our study, just as in the case of Wnt-mediated Axin inactivation, SKL2001 inhibited both the CK1-and GSK-3β-mediated phosphorylation of β-catenin at Ser45 and Ser33/37/Thr41, respectively, in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This structure forms a rigid scaffold for the binding of many factors, including the Tcf transcription factor, the cell adhesion protein cadherin, APC, Axin and others (Graham et al, 2000(Graham et al, , 2002Huber and Weis, 2001; Spink et al, 2001;Xing et al, 2003Xing et al, , 2004Ha et al, 2004;Liu et al, 2006). Surprisingly, many of these factors bind the same two lysine residues in repeats 5 and 8, which we have called the 'charged buttons' since they serve a major role in attaching partners to b-catenin via electrostatic interactions (Graham et al, 2000). The N-and C-terminal regions are much smaller, and appear to form mostly flexible regions that primarily interact with transcriptional activating factors.…”
Section: B-cateninmentioning
confidence: 99%
“…Residues that are conserved among other bilaterians but have changed in vertebrate betacatenin or plakoglobin are red. Note that: (1) one change has occurred in this particular region of vertebrate beta-catenin (arrowhead); and that (2) hot spots for interaction with cadherin, Axin, APC, and TCF factors have been identified at these repeats, especially the acidic groove, in mouse/human beta-catenin (Graham et al, 2000;von Kries et al, 2000;Huber and Weis, 2001). Strong, stabilizing selection is most likely imposed by essential intra-and intermolecular interactions that account for the structural and functional properties of beta-catenin.…”
Section: Structural Context Of Conserved Residuesmentioning
confidence: 99%
“…These residues are conserved in Ce Hmp-2 and all bilaterian beta-catenins but have changed in both Ce Bar-1 and Ce Wrm-1. However, structural analyses of TCF/beta-catenin and cadherin/ beta-catenin complexes indicate that beta-catenin utilizes some of the same residues in R5-R8 to interact with both TCF and cadherins (Graham et al, 2000;Huber and Weis, 2001). Therefore, signaling and adhesion constraints may be superimposed on some of the same residues, explaining their conservation in both Ce Hmp-2 and Ce Bar-1.…”
Section: Loss Of Constraints In C Elegans Beta-cateninsmentioning
confidence: 99%
See 1 more Smart Citation